Adaptations of Operating Structures of Government Administrative Organizations - Joiner, Charles A. (Academy of Management Journal, 1961)
Significance of the political implications of changing the operating structure of a government unit; Conditions warranting structural changes as efficient; Methodological aspects of analyzing operating structures in government administrative organizations.